THE ENHANCEMENT OF CONSTRUCT ARGUMENTS AND GIVE REASONS IN SALT HYDROLISIS LESSON BY GUIDED INQUIRY LEARNING MODEL - Ari Kurnia Efendi; Ila Rosilawati; Noor Fadiawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
This research aims to describe the effectiveness and characteristics of guided inquiry learning model in salt hydrolysis lesson to improve the skills of constructing arguments and giving reasons. Populations in this research is all students of State senior high school 1 Gadingrejo even semester of Academic Year 2011-2012 with XI Science 3 class and XI Science 4 class as sample. This research uses a quasi-experimental methods Non Equivalent Control Group Design. The effectiveness of guided inquiry learning model is measured by an increase in significant N-gain. Results showed N-gain average of construct argument skills for the experimental class and control class respectively 0.61 and 0.35; and N-gain average of give reason skills for the experimental class and control class respectively 0.56 and 0,29. Testing the hypothesis in this research using two average difference test with the t-test statistical formula. The results of hypothesis testing showed the skill of construct arguments and give reasons students on salt hydrolysis lesson that is applied guided inquiry learning model is higher than those applied to conventional learning. Based on the results of hypothesis testing, it was concluded that guided inquiry learning model is effective in improving the skills of construct arguments and give reasons on salt hydrolysis lesson. Keywords: guided inquiry learning model, construct argument skills, give reasons skills